Host‐Guest Interaction in Ethylene and Ethane Separation on Zeolitic Imidazolate Frameworks as Revealed by Solid‐State NMR Spectroscopy. Issue 44 (29th June 2021) - Xiao, Yuqing; Chu, Yueying; Li, Shenhui; Chen, Fang; Gao, Wei; Xu, Jun; Deng, Feng
Abstract: The separation of ethane/ethylene mixture by using metal‐organic frameworks (MOFs) as adsorbents is strongly associated with the pore size‐sieving effect and the adsorbent‐adsorbate interaction. Herein, solid‐state NMR spectroscopy is utilized to explore the host‐guest interaction and ethane/ethylene separation mechanism on zeolitic imidazolate frameworks (ZIFs). Preferential access to the ZIF‐8 and ZIF‐8‐90 frameworks by ethane compared to ethylene is directly visualized from two‐dimensional 1 H‐ 1 H spin diffusion MAS NMR spectroscopy and further verified by computational density distributions. The 1 H MAS NMR spectroscopy provides an alternative for straightforwardly extracting the adsorption selectivity of ethane/ethylene mixture at 1.1∼9.6 bar in ZIFs, which is consistent with the IAST predictions. Abstract : 1 H MAS NMR experiment of ethane/ethylene mixtures adsorbed on ZIFs facilitates the precise determination of the adsorption selectivity. The adsorbent‐adsorbate interactions between ethane/ethylene and ZIFs are directly visualized from two‐dimensional 1 H‐ 1 H spin diffusion solid‐state NMR spectroscopy. Host‐Guest Interaction in Ethylene and Ethane Separation on Zeolitic Imidazolate Frameworks as Revealed by Solid‐State NMR Spectroscopy (Deng)